“Green Destination Tourism” Reviewed from Islamic Economic Perspective (Case Study in Pulesari Yogyakarta Tourist Village) - Robist Hidayat; Taufik Riza Mahendra; Intan Octavia (Majalah Ilmiah Bijak, 2020)
Natural tourism villages usually carry the concept of "go green and back to nature." One of the tours that apply this concept is in the Pulesari village, Yogyakarta, where it carries the concept of green tourism, which is one of the "green destination tourism spots." Therefore, the idea is interesting, especially on the impact of "green destination tourism," besides the phenomenon of "halal destination tourism." The phenomenon occurs due to the Indonesian topography, especially Yogyakarta. Since it is a tropical region, and currently the development of the Islamic economy is positive, leading to researchers conducting research on "green destination tourism," which is reviewed in an Islamic economic perspective and showing that the tourism village applies Islamic economic concepts where the transaction is far from gharar (unclear matter). Thus it has a positive impact and one of the alternative choices for the development of the "tourism industry sector" in accordance with Islamic sharia of transparent transactions without additional stuff. The method used by the researcher was a qualitative method, in which the researcher conducted a survey directly to tourist attractions to do interviews.